2014
DOI: 10.1177/0095327x14536710
|View full text |Cite
|
Sign up to set email alerts
|

Status- and Stigma-related Consequences of Military Service and PTSD

Abstract: This article describes an experimental study that investigates the status-and stigma-related consequences of military service and of experiences in war resulting in posttraumatic stress disorder (PTSD). In the study, participants interacted with fictitious partners whom they believed were real in four conditions: a control condition, a condition in which the ''partner'' was in the military, a condition in which the ''partner'' was a war veteran who had been deployed to Iraq or Afghanistan, and a condition in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…We suspect that in addition to men and women facing different categorization assumptions based on their sexual behavior, they will also be differentially stigmatized. Status and stigma processes share considerable conceptual and empirical overlaps, with low-status groups also more likely to be stigmatized (Hipes, Lucas, and Kleykamp 2015;Lucas and Phelan 2012). Consistent with the idea that status and stigma tend to co-vary, in exploratory analyses we found that not only are heterosexual men stripped of assumptions of heterosexuality more quickly than are heterosexual women, but they are also more stigmatized for that behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that in addition to men and women facing different categorization assumptions based on their sexual behavior, they will also be differentially stigmatized. Status and stigma processes share considerable conceptual and empirical overlaps, with low-status groups also more likely to be stigmatized (Hipes, Lucas, and Kleykamp 2015;Lucas and Phelan 2012). Consistent with the idea that status and stigma tend to co-vary, in exploratory analyses we found that not only are heterosexual men stripped of assumptions of heterosexuality more quickly than are heterosexual women, but they are also more stigmatized for that behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the negative dimension of public perceptions of veterans results from media accounts that often focus on veterans coping with traumatic brain injuries, PTSD, and instances of political extremism and unstable behavior (Hipes, Lucas, and Kleykamp 2015). Well-intentioned public campaigns to raise awareness of veterans’ issues (e.g., suicide) can enhance misperceptions that lead to overt and subtle forms of discrimination as well as internalized stigma among veterans.…”
Section: Introductionmentioning
confidence: 99%
“…The US public endorses positive attitudes toward military service members and veterans of the Armed Forces (Hipes et al, 2015), which consistently ranks as one of the most trusted institutions in the United States (Johnson, 2018) despite the unpopularity of the wars in Iraq and Afghanistan. Indeed, veterans are so popular among the American public that it could be socially undesirable to express opinions that portray veterans in a negative light.…”
Section: Public Attitudes Toward Military Veteransmentioning
confidence: 99%
“…Indeed, veterans are so popular among the American public that it could be socially undesirable to express opinions that portray veterans in a negative light. Scholars have described a "Support the Troops" norm in US society and an empirical study (Hipes et al, 2015) reported that the American public does indeed overstate its support for members of the Armed Forces because of social norms. Even after accounting for normative responses, however, respondents generally describe veterans in primarily positive terms (Hipes et al, 2015).…”
Section: Public Attitudes Toward Military Veteransmentioning
confidence: 99%